Direct intramyocardial transthoracic transplantation of bone marrow mononuclear cells for non-ischemic dilated cardiomyopathy: INTRACELL, a prospective randomized controlled trial - Sant'Anna,Roberto T. (2014)
Objective: We tested the hypothesis that direct intramyocardial injection of bone marrow mononuclear cells in patients with non-ischemic dilated cardiomyopathy can improve left ventricular function and physical capacity. Methods: Thirty non-ischemic dilated cardiomyopathy patients with left ventricular ejection fraction <35% were randomized at a 1:2 ratio into two groups, control and treated. The bone marrow mononuclear cells group received 1.06±108 bone marrow mononuclear cells through mini-thoracotomy. There was no intervention in the control group. Assessment was carried out through clinical evaluations as well as a 6-min walk test, nuclear magnectic resonance imaging and echocardiogram. Results: The bone marrow mononuclear cells group showed a trend toward left ventricular ejection fraction improvement, with magnectic resonance imaging - at 3 months, showing an increase from 27.80±6.86% to 30.13±9.06% (P=0.08) and returning to baseline at 9 months (28.78%, P=0.77). Magnectic resonance imaging showed no changes in left ventricular ejection fraction during follow-up of the control group (28.00±4.32%, 27.42±7.41%, and 29.57±4.50%). Echocardiogram showed left ventricular ejection fraction improved in the bone marrow mononuclear cells group at 3 months, 25.09±3.98 to 30.94±9.16 (P=0.01), and one year, 30.07±7.25% (P=0.001). The control group showed no change (26.1±4.4 vs 26.5±4.7 and 30.2±7.39%, P=0.25 and 0.10, respectively). Bone marrow mononuclear cells group showed improvement in New York Heart Association functional class, from 3.40±0.50 to 2.41±0.79 (P=0.002); patients in the control group showed no change (3.37±0.51 to 2.71±0.95; P=0.17). Six-minute walk test improved in the bone marrow mononuclear cells group (348.00±93.51m at baseline to 370.41±91.56m at 12 months, P=0.66) and there was a non-significant decline in the control group (361.25±90.78m to 330.00±123.42m after 12 months, P=0.66). Group comparisons were non-significant. Conclusion: The trend of intragroup functional and subjective improvement was not confirmed when compared to the control group. Direct intramyocardial application of bone marrow mononuclear cells in non-ischemic dilated cardiomyopathy was not associated with significant changes in left ventricular function. Differences observed within the bone marrow mononuclear cells group could be due to placebo effect or low statistical power.